2023
DOI: 10.1590/1519-6984.272003
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvic acid as attenuator of water deficit in cotton plants varying the phenological stage

Abstract: The lack of water during crop growth causes damage to any production system, especially when it occurs during the initial establishment or beginning of the reproductive stage. Although cotton can be properly managed in regions with water limitation, its yield is affected at different levels according to the genetics of the cultivar adopted. Exogenous application of some organic components has shown a stress-mitigating effect and can be a valuable procedure to enhance the yield of water stress-sensitive cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…BR1. In another study, Silva et al (2023) evaluated the benefits of exogenous pyruvic acid (100 µM) in cotton plants under water deficit and observed that the pyruvate attenuated the effects of water suppression on boll production by 31% in the cv. BRS Seridó and by 34% in the cultivars CNPA 7MH and FM 966.…”
Section: Resultsmentioning
confidence: 99%
“…BR1. In another study, Silva et al (2023) evaluated the benefits of exogenous pyruvic acid (100 µM) in cotton plants under water deficit and observed that the pyruvate attenuated the effects of water suppression on boll production by 31% in the cv. BRS Seridó and by 34% in the cultivars CNPA 7MH and FM 966.…”
Section: Resultsmentioning
confidence: 99%
“…Although the negative effects of water stress on fluorescence emission and the photosynthetic pigment content of sugarcane plants are well reported in the literature [12][13][14][15], there are reports that organic substances can mitigate the harmful effects of drought by increasing the ability of plants to withstand such deleterious conditions, e.g., studies of pyruvate application carried out with peanuts [16] and cotton [17,18]. However, research focusing on the photosynthetic apparatus of sugarcane plants has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%